BNNT-ZnO QDs nanocomposites for improving piezoelectric nanogenerator and piezoelectric properties of boron nitride nanotube. (March 2022) - Shim, Jaeho; Son, Dong Ick; Lee, Joo Song; Lee, Jaehyeon; Lim, Guh-Hwan; Cho, Hyunjin; Kim, Eun-young; Bu, Sang Don; IM, Sungbin; Jeong, Chang Kyu; Rezvani, Sina; Park, Simon S.; et al.
Abstract: Boron nitride nanotubes (BNNTs) are eco-friendly and lightweight materials with various physical, chemical, piezoelectric and mechanical properties. In particular, their exceptional properties can be exploited for piezoelectric applications. However, it remains a great challenge to improve the efficiency of the piezoelectric properties in the radial direction rather than the longitudinal direction. Thus, design with BNNT-inorganic composite materials is required including the outstanding inorganic piezoelectric materials to induce the improved performance of the piezoelectric properties. Here, we suggest the high-performance piezoelectric device as a nanogenerator based on BNNT-ZnO quantum dots (QDs) nanocomposites. The ZnO QDs were chemically synthesized on the surface of BNNTs by hydrothermal synthesis. As to the critical piezoelectric properties, we have investigated piezoelectric constants of BNNT-ZnO QDs nanocomposites and the difference in piezoelectric properties between out-of-plane and in-plane through conventional piezoelectric force microscopy (PFM) analysis. In addition, we confirmed the piezoelectric effect generated by applying a specific force to the single wire of BNNT-ZnO QDs nanocomposites in the radial direction using in-situ hybrid SEM-PFM technique. The effective piezoelectric coefficient ( d 33 ) of the single wire of BNNT-ZnO QDs in the radial direction and the piezoelectric charge coefficient of BNNT-ZnO QDs films were increased by 42.8% (0.340 pm/V) and 41.9% (−60.3 pC/N), respectively, compared to that of the single wire of BNNT and BNNT films. BNNT-ZnO QDs nanocomposites based transparent and flexible piezoelectric device showed excellent piezoelectric properties with a small amount of 0.18 wt%. The piezoelectric performance of nanogenerator with electrically poled BNNT-ZnO QDs nanocomposites was improved by more than 140% and 45%, respectively, compared to those of intrinsic BNNT-ZnO QDs nanocomposites and BNNT. Therefore, this study will pave a new path to the development of innovative materials and devices to generate recycled energy. Graphical Abstract: ga1 Highlights: The high-performance piezoelectric device as a nanogenerator based on BNNT-ZnO quantum dots (QDs) nanocomposites. Chemical bonding formation by electrostatic interaction between surface of BNNT and surface of ZnO QD. The piezoelectric coefficient of BNNT-ZnO QDs increases compared to that of the BNNT. The characteristics of piezoelectric device based on BNNT-ZnO QDs increases compared to that of the BNNT.